A influência do gerenciamento de projetos em transferências voluntárias de recursos da união para municípios brasileiros: o caso de uma prefeitura de médio porte - Moutinho, José da Assunção (2012)
The assignments redefinition of the Brazilian government spheres, introduced with the advent of the Federal Constitution in 1988, involves an intense process of migrating of Union resources to the municipalities. Despite the tax increasing revenue, the municipal sphere needs extra resources to meet the local growing demands and expects voluntary transfers envisions for this possibility. In this way, to develop projects aiming to raise funds and manage them effectively is vital to the realization of the needs of the population. However, the introduction of practices in project management, innovating the public environment, implies the definition of new paradigms guided by results. In this way, the study aims to identify how the practices of those project management influence the process of voluntary transfers of resources in Brazilian midsize municipalities. The research is based on literature that concerns about the decentralization of resources of the Union to the municipality, the presence of project management practices in public administration and deployment of project offices as drivers of success. The methodological procedure used in this research relies on the case study as a research strategy, guided by a set of theoretical propositions. The empirical evidence indicate the search for the action s effectiveness used, carried out by the Office Project, strategically positioned as an integrator instrument between the different projects and responsible for dissemination of management practices project in the municipal public environment. When analyzed on the light of these practices, the search results shows the emphasis the System Management Transfer Agreements and Contracts - SICONV - as the enabling environment of voluntary transfers, to certain areas of knowledge during the different phases of the life cycle project. In the initial phase, characterized by the proposition, celebration and formalization of the agreement, management of costs and acquisitions receives increased emphasis. In the subsequent phase, defined as execution and monitoring, we highlight the scope, acquisitions and integration areas. Now at the stage for accountability, the environment owns up to proof of the correct application of financial resources and the achievement of the objectives initially agreed. The study also indicates the need for a qualitative leap forward of the practices adopted by the main parties involved (ministries, municipalities and financial agents) in the management of voluntary transfers.